2021
DOI: 10.26434/chemrxiv.14555841.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increasing the CO2 Reduction Activity of Cobalt Phthalocyanine by Modulating the σ-donor Strength of Axially Coordinating Ligands

Abstract: <p>Axial coordination of a pyridyl moieties to CoPc (either exogenous or within poly-4-vinylpyridine polymer) dramatically increases the complex’s activity for CO<sub>2</sub>RR. It has been hypothesized that axial coordination to the Co active site leads to an increase in the Co dz<sup>2</sup> orbital energy, which increases the complex’s nucleophilicity and facilitates CO<sub>2</sub> coordination compared to the parent CoPc complex. The magnitude of the energy increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…In our prior work in this area, we immobilized CoPc−P4VP and related systems onto edge-plane graphite (EPG) electrodes to form CoPc−P4VP/EPG materials. 13,36,44,47 In these previous studies, we sought to understand the microenvironment surrounding the polymer-encapsulated CoPc site. EPGs were an optimal choice of electrode because the high surface area of the electrode surface and intercalation of the CoPc catalyst between the graphitic sheets facilitated charge transport to the CoPc active sites.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our prior work in this area, we immobilized CoPc−P4VP and related systems onto edge-plane graphite (EPG) electrodes to form CoPc−P4VP/EPG materials. 13,36,44,47 In these previous studies, we sought to understand the microenvironment surrounding the polymer-encapsulated CoPc site. EPGs were an optimal choice of electrode because the high surface area of the electrode surface and intercalation of the CoPc catalyst between the graphitic sheets facilitated charge transport to the CoPc active sites.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…CoPc(pyNMe 2 )−P2VP/GP suspensions were prepared via sonication of 0.0052 g of CoPc and 1.0995 g of 4-(dimethylamino)pyridine in 45 mL of DMF for 1 h in an aluminum foil-jacketed polypropylene conical centrifuge tube (Basix) to form a 0.2 mM CoPc/0.2 M pyNMe 2 /DMF solution, ensuring 5coordinate character using a 1000:1 pyNMe 2 :CoPc ratio, as we have done previously. 44 This solution was then diluted to 1 mL of the desired CoPc and pyNMe 2 concentration via the addition of the stock solution to DMF in a 20 mL scintillation vial. A given mass of P2VP was then added to the 20 mL scintillation vial that contained 1 mL of CoPc/DMF in order to form the desired CoPc(pyNMe 2 )−P2VP solution, which was then sonicated for 30 min to ensure the dispersion of P2VP.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In a combined experimental and computational study, we showed that increasing the σ-donor ability of the axial ligand (L) results in an increase in the CO 2 RR activity by CoPc(L) (Figure 5). 4 Computational studies confirmed that the strength of the σ-donor ability was correlated with the relative energy of the d z 2 orbitals, that the HOMO of the pertinent reduced [CoPc(L)−CO 2 ] − involves an interaction between the d z 2 orbital and the CO 2 adduct, and that mechanism 1 in Figure 4a is likely the operative mechanism under our CO 2 RR conditions. 4 In our studies of the polymer-encapsulated CoPc systems, we have been unable to isolate the secondary coordination sphere effects from other polymer effects.…”
Section: Ligand Sphere Effects: Primary and Secondary Coordination Sp...mentioning
confidence: 99%
“…4 Computational studies confirmed that the strength of the σ-donor ability was correlated with the relative energy of the d z 2 orbitals, that the HOMO of the pertinent reduced [CoPc(L)−CO 2 ] − involves an interaction between the d z 2 orbital and the CO 2 adduct, and that mechanism 1 in Figure 4a is likely the operative mechanism under our CO 2 RR conditions. 4 In our studies of the polymer-encapsulated CoPc systems, we have been unable to isolate the secondary coordination sphere effects from other polymer effects. However, the increased activity of CoPc−P4VP and CoPc(py)−P2VP compared to CoPc(py) provide circumstantial support for the role of secondary-coordination sphere effects in enhancing catalytic activity.…”
Section: Ligand Sphere Effects: Primary and Secondary Coordination Sp...mentioning
confidence: 99%
See 1 more Smart Citation